Research Status and Development Trend of Non-circular Gears - Wu Song; Zhang Xiangjun; Fu Xuezhong; Huang Yuanxing; Li Jingzhen (Jixie chuandong)
Non-circular gear transmission is a new type of mechanical transmission mechanism relative to circular gear transmission, which can realize special movement, improve mechanism performance and improve mechanism motion conditions. With the improvement of non-circular gear transmission design ability and the increase of application scope, the research on non-circular gear transmission is increasing. This study introduces the current research status of non-circular gear transmission applications, summarizes the research progress of non-circular gear transmission design and analysis, discusses the methods and strategies for manufacturing non-circular gear drives, summarizes the problems faced by the current development of non-circular gear transmission, and looks forward to the research directions of non-circular gear transmission in applications, design and analysis, and processing and manufacturing.